Pemanfaatan Zeolit Alam Ende Sebagai Katalis dalam Pirolisis Polietilena dari Sampah Plastik - Gregorio Antonny Bani (Jurnal Riset Kimia, 2023)
Pyrolysis is one way to minimise plastic waste. This process requires a catalyst such as zeolite. Natural zeolite needs to be activated to increase its catalytic activity. Therefore, this research was carried out by activating Ende's natural zeolite using 1% hydrofluoric acid (HF), 6M hydrochloric acid (HCl), and 1M ammonium chloride (NH4Cl) to be used as catalysts in the pyrolysis of polyethylene from plastic waste. Pyrolysis was carried out at operating temperatures of 300 oC, 350 oC, 400 oC, and 450 oC, and treated with a catalyst composition of 0%, 5%, 10%, and 15% from 1000 grams of polyethylene. Based on the results of the study, it was concluded that activation of Ende's natural zeolite could change the chemical and physical properties of Ende's natural zeolite, including crystallinity, surface area, pore volume, and pore radius, and acidity to serve as a catalyst. Treatment of 10% catalyst from 1000 mg of plastic at an operating temperature of 400oC reduced the activation energy to 4.371.1 cal/mol and produced 80% more paraffin fraction in polyethylene pyrolysis oil from plastic waste.